(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of this study is to ascertain why electronic databases are used, how often they are used, how satisfied users are with their experience, and what issues users have when trying to access the electronic databases at the central library of Hemwati Nandan Bahuguna Garhwal University in Uttarakhand. Faculty members and research experts were surveyed, and the results were examined. Based on this analysis, the study found that faculty members and research scholars primarily used electronic databases including Springer Link, Taylor & Francis, and Science Direct. The results showed that in order to improve the use of the university’s existing databases, user education and information literacy programs are required.